Prevalence and Determinants of Pregnancy‐Induced Hypertension Among Women Attending Antenatal Care in Asella Town, Southeast Ethiopia: A Cross‐Sectional Study - Birtukan Ahmed; Ayalneh Demissie; Biniam Belete; Addis Wordofa; Helen Bekele; Tesfa Gebremeskel (Health Science Reports, 2026)
ABSTRACT Background and Aims Pregnancy‐Induced Hypertension (PIH) is a primary contributor to global maternal and perinatal mortality. This study determined the prevalence of PIH and identified its modifiable and non‐modifiable determinants among pregnant women attending antenatal care (ANC) in Asella Town, southeast Ethiopia. Methods A facility‐based cross‐sectional study was conducted in December 2023 across three public health facilities. Systematic random sampling selected 834 pregnant women with a gestational age greater than 20 weeks. Data were collected through structured interviewer‐administered and medical chart reviews. Statistical analyses were performed using STATA Software, version 17.0 (StataCorp LLC, College Station, TX, USA). Variables with a p ‐value less than 0.25 in bivariable analysis were fitted into a multivariable logistic regression model. Statistical significance was declared at a two‐sided p ‐value less than 0.05. Results Of 834 sampled individuals, 794 completed the study (95.2% response rate). The PIH prevalence was 5.2% (95% CI: 3.7%, 7.0%). Multivariable analysis identified several factors associated with higher odds of PIH: no formal education (AOR = 5.44, 95% CI: 1.47–20.19), multiple pregnancy (AOR = 3.69, 95% CI: 1.07–12.7), family history of chronic hypertension (AOR = 4.04, 95% CI: 1.51–10.8), presence of edema (AOR = 3.84, 95% CI: 1.37–10.7), and alcohol consumption within the past 12 months (AOR = 6.19, 95% CI: 1.11–34.4). Conversely, receiving nutritional counseling during ANC was associated with reduced odds of developing PIH (AOR = 0.27, 95% CI: 0.09–0.79). Conclusions PIH remains a notable health concern among pregnant women in Asella town, showing prevalence comparable to national averages. The identified factors emphasize the interplay between non‐modifiable traits and modifiable behaviors. Strengthening routine ANC services through standardized nutritional counseling may serve as an effective, accessible preventive approach in low‐resource primary care settings.